Chapter Order is what states make of it. Interregnum, world-scale problems, and multilateralism - ATTINA', Fulvio (Studi e saggi, 2022)
The present chapter assumes that using multilateralism to address world-scale problems has an impact on the future of world politics and may be the game-changer of the world political order. In the first section, attention is drawn to the establishment of the present world order, the multilateral institutions and policies that have been the cornerstone of such order, and the current order transition process. Based on the research knowledge about the ongoing world climate policymaking process, the second section explains the persistent role of multilateral policymaking as the way of responding to the problems that are widespread over the entire planet and are inherent to the structure of the world polity of the sovereign states.